Modified GTS Allocation Scheme for IEEE 802.15.4 - Darmawan, Zakha Maisat Eka; Al Rasyid, M. Udin Harun; Sudarsono, Amang (Politeknik Elektronika Negeri Surabaya (PENS), 2015)
IEEE 802.15.4 standard is widely used in wireless personal area networks (WPANs). The devices transmit data during two periods: contention access period (CAP) by accessing the channel using CSMA/CA and contention free period (CFP), which consists of guaranteed time slots (GTS) allocated to individual devices by the personal area network (PAN). However, the use of GTS slot size may lead to severe bandwidth wastage ifÂ the traffic pattern is not fit or only a small portion of GTS slot is used by allocated device. The proposed scheme devides the GTS slot and then optimizes the GTS slot size by exploiting the value of superframe order (SO) information. The proposed scheme was tested through simulations and the results show that the new GTS allocation scheme perform better than the original IEEE 802.15.4 standard in terms of average transmitted packets, throughput, latency and probability of successful packets.